Description of a new species of Cephalaeschna (Odonata: Anisoptera: Aeshnidae) from northern Vietnam - Sasamoto, Akihiko; Lien, Vu Van (Zootaxa, 2018)
A new aeshnid species, Cephalaeschna yanagisawai sp. nov. from northern Vietnam (Hoang Lien National Park, Lai Chau Province, 103°45’E, 22°20’N, 1900 2000 m a.l.s.), is described and illustrated. This species can be differentiated from the other species of the genus by body maculation, the morphology of the male anal appendages, and female postero-ventral S10 tergite projecting posteriorly, which is a rare feature in the genus.